Integrating Target Language Culture Into Teaching-Learning EFL - Riadhul Marhamah; Bukhari Daud; Iskandar Abdul Samad (English Education Journal, 2017)
An important aspect of learning a language is to learn the culture of the language. The actual relationship between the two cannot be separated, because a language serves a particular culture and through the language the cultural values of a people are reflected. Therefore, the role of English teachers is very important in the teaching of language and culture that should always be linked together in the teaching-learning of language. The purpose of this study was to discover the perceptions of EFL teachers on integrating teaching-learning about English culture into EFL classrooms and to investigate whether or not the EFL teachers supported acquisition of cross-cultural understanding by their students. To get their results, the researchers collected data from observations in three English classrooms to look at the integration of teaching-learning about culture into the EFL teaching-learning processes. After the observations, the researchers interviewed the three teachers about the integration of culture into the EFL classroom. Then the researchers analyzed, condensed and displayed the data and drew conclusions. The results of this study showed that the EFL teachers were aware of the importance of studying the English culture but one of them did not yet focus on integrating English culture into teaching-learning EFL. This was  due to several factors such as the lack of English language knowledge of the teacher and insufficient time for teaching theory and language structures.